Reconstruction of Language Learning in Universities in the Post Covid-19 - Mohammad Ilyas (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Background: After the Covid-19 pandemic forced educational institutions to change learning methods and techniques, especially at universities in Indonesia, because face-to-face meetings have been carried out in stages. This research generally aims to describe the Reconstruction of Indonesian Language Learning in Post-Covid-19 Universities. Methodology: This study uses the literature review method, searching and researching literature by reading various books, journals, and other publications. Findings: The findings of this study include post-covid-19 brings good benefits in terms of online-based learning, which is undoubtedly one of the demands of digitalization of education today. The strategy that can be used in reconstructing Indonesian learning after COVID-19 is to use the Blended Learning method, namely by a combination of learning models carried out in online and offline contexts; Supporting factors that exist in reconstructing Indonesian language learning in universities after the covid-19 pandemic include: students are accustomed and trained in online learning which is nothing but the demands of the era of digitalization of education at this time; besides that it can also trigger the acceleration of transformation for the world of education in Indonesia; the emergence of online learning applications as a learning reference that supports students; the spread of free online courses and the emergence of unlimited creativity; By studying online at home, students can at least apply it to their home environment. Conclusion: The obstacle in reconstructing Indonesian language learning at universities in the context of digitizing education at this time is the limited facilities and infrastructure in the form of internet quotas, internet signals or networks, wifi, facilities and infrastructure, response, and technology. Moreover, maximizing the blended learning method is the right strategy for overcoming the Various Obstacles in Reconstructing Indonesian Language Learning in Post-Covid-19 Universities.